Kinematics of Faster Acceleration Performance of the Quick Single in Experienced Cricketers. Issue 9 (September 2015) - Callaghan, Samuel J.; Lockie, Robert G.; Jeffriess, Matthew D.; Nimphius, Sophia
Abstract : Abstract: Callaghan, SJ, Lockie, RG, Jeffriess, MD, and Nimphius, S. Kinematics of faster acceleration performance of the quick single in experienced cricketers. J Strength Cond Res 29(9): 2623–2634, 2015—The introduction of the shorter match formats for cricket (i.e., Twenty20) requires batsmen to be proficient in sprint acceleration to increase run scoring potential. Therefore, the study aim was to identify the kinematics of faster acceleration performance of nonstriking batsmen when completing a quick single. Eighteen experienced male cricketers currently playing cricket in a regional competition in Australia completed 17.68-m sprints using a match-specific start (walking start, bat dragged through crease, leg guards worn). Timing gates recorded the 0–5 and 0–17.68 m time. Joint and step kinematics were analyzed through the first and second steps through 3-dimensional motion analysis. Subjects were split into faster and slower groups according to 0- to 5-m time, and a 1-way analysis of variance determined significant ( p ⩽ 0.05) between-group differences. Effect sizes and Pearson's correlations ( r ) were also calculated. The faster group was significantly quicker for the 0–5 and 0–17.68 m intervals and had a 10% longer first, and 11% longer second, step. Second step swing leg hip adduction was 23% greater in the faster group. A significant negative correlation ( r = −0.647) was found between second step drive leg extension and 0- to 5-m time. Batsmen should cover the initial 5 m of a quick single in the shortest time possible to increase the likelihood of a successful run. This is aided by longer first and second steps and increased hip adduction to transition into normal sprint technique. Step length development should be a key consideration for coaches attempting to improve quick single performance. Abstract : Supplemental Digital Content is Available in the Text.